Conjugation Inhibitors and Their Potential Use to Prevent Dissemination of Antibiotic Resistance Genes in Bacteria - Cabezón, Elena; de la Cruz, Fernando; Arechaga, Ignacio (Frontiers in Microbiology, 2017)
Antibiotic resistance has become one of the most challenging problems in health care. Bacteria conjugation is one of the main mechanisms whereby bacteria become resistant to antibiotics. Therefore, the search for specific conjugation inhibitors is of interest in the fight against the spread of antibiotic resistances in a variety of laboratory and natural environments. Several compounds, discovered as conjugation inhibitors (COINs), are promising candidates in the fight against plasmid dissemination. In this review, we survey the effectiveness and toxicity of the most relevant compounds. Particular emphasis has been placed on unsaturated fatty acid derivatives, as they have been shown to be efficient in preventing plasmid invasiveness in bacterial populations. Biochemical and structural studies have provided insights concerning their potential molecular targets and inhibitory mechanisms. These findings open a new avenue in the search of new and more effective synthetic inhibitors. In this pursuit, the use of structure-based drug design (SBDD) methods will be of great importance for the screening of ligands and binding sites of putative targets.